ASSOCIATION OF NOCTURNAL BLOOD PRESSURE PATTERNS WITH CARDIOVASCULAR RISK IN NEWLY DIAGNOSED, NEVER-TREATED ESSENTIAL HYPERTENSIVE PATIENTS. (June 2018) - Dolgyras, P.; Anyfanti, P.; Gkaliagkousi, E.; Lazaridis, A.; Triantafyllou, A.; Nikolaidou, B.; Koletsos, N.; Zarifis, I.; Zamboulis, C.; Douma, S.
Abstract : Objective: Both non-dipping pattern and elevated nighttime systolic blood pressure (SBP) are predictors of adverse cardiovascular outcomes. Despite the fact that these are often related features, research to date has focused on the association of either with cardiovascular risk, as separate features. We assessed whether the combination of a dipping pattern with abnormal nighttime SBP confers increased cardiovascular risk for patients with essential hypertension Design and method: Newly diagnosed, never-treated hypertensive patients free from any known health problems were eligible to participate. Only true hypertensives, based on their office blood pressure measurements and the 24-hour ambulatory blood pressure monitoring, were included. 10-year risk of general cardiovascular disease was determined from the Framingham Heart Study. Results: In a total of 182 patients aged 46.7 ± 8.8 years, nighttime SBP positively correlated with cardiovascular risk (r = 0.190, p = 0.010). Initially, patients were classified according to their dipping status as dippers (n = 117) and non-dippers (n = 65). The groups did not differ in terms of age, gender, body mass index (BMI), office blood pressure, smoking, and lipids (p > 0.05 for all comparisons). Cardiovascular risk [9.8 (6.3–15.9) vs 10.3 (6.5–15.2) %, p = 0.981] was similar between dippers and non-dippers. Participants were then classified in three groups, based on the combination of dipping status with nighttime SBP: dippers with normal nighttime SBP (n = 45), dippers with elevated nighttime SBP (n = 72), and non-dippers (n = 65). Age, gender, BMI, smoking status, and lipids were similar between groups (p > 0.05 for all comparisons). However, dippers with normal nighttime SBP exhibited the lowest levels of office SBP (144.1 ± 13.5 vs 153.0 ± 15.2 vs 151.9 ± 14.9 mmHg, p = 0.004) and, importantly, the lowest cardiovascular risk score [8.4 (5.8–12.9) vs 11.6 (7.7–18.6) vs 10.3 (6.5–15.2) %, p = 0.050], compared to dippers with abnormal nighttime SBP and non-dippers. Conclusions: In a population of relatively young, untreated patients with uncomplicated, early-stage essential hypertension, the combination of a dipping profile with elevated nighttime SBP confers the same cardiovascular risk as the non-dipping pattern. Subsequently, further classification of dippers according to their nighttime SBP levels may improve cardiovascular risk stratification.